(3cJGH aj Gdadcs - (3HWdjehS GdMcje GdbdhPjs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYOd hhGgH GdYbd bGd HWdjehS Yde GdfLhe efc hefgG s
(3BNQgG (B:s
(3aEPG hLOJ GdOhGH jSjQ SjQI hEfc ef GdeZQH Edi GdeTQb aEf GdNGQLi jCJi ef HYO Edi GdCbGdje hEf de jcf SGFQ aEf GdNGQLi ef MVQI GdCbdje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdcJGH YHGQI Yf MGTjI Ydi cJGH aGQSjs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs